(untitled) (Samsad Journal संसद जर्नल, 2024)
Cooperative federalism has emerged as a pivotal concept in governance structures worldwide, facilitating collaboration and coordination among various levels of government. In the context of Nepal, the adoption of federalism represents a significant shift in the country’s political landscape, aiming to address historical grievances, promote inclusivity, and foster socio-economic development. This essay provides a detailed examination of cooperative federalism within the framework of the Constitution of Nepal. Through an in-depth analysis of constitutional provisions, historical background, implementation challenges, and case studies, this essay elucidates the role of cooperative federalism in promoting unity, diversity, and equitable development in Nepal. By identifying key opportunities and obstacles, this study offers insights into the prospects for effective governance and democratic consolidation in the federal structure of Nepal.